KEUNGGULAN BERSAING UMKM KULINER BERBASIS INOVASI (STUDI PADA UMKM KERIPIK SAMILER KASPER DI SIDOARJO) - Endang Siswati; Ramadhan Alfiansyah (IDEI: Jurnal Ekonomi & Bisnis, 2020)
This research was conducted in Sidoarjo, namely in the "Kasper" Samiler Crackers business which aims to determine the innovation strategy and competitive advantage of the Kasper Samiler Crackers. This research is a research that uses a qualitative approach. Which uses interview and observation instruments. Data collection techniques using observation, interview, documentation and triangulation techniques. The results showed that the innovations made by Samiler Casper Crackers were innovations in products, processes, organizations, and innovations in marketing strategies, which were in line with Oslo theory. The innovation strategy undertaken by Casper is very supportive in competitive advantage so that the company is able to compete with similar products so as to increase its sales onset.